Expression of peptide receptors in human endocrine tumours of the pancreas. Issue 2 (February 1997) - Tang, C; Biemond, I; Lamers, C B
Abstract : BACKGROUND: Gut peptides are known to influence hormone release and growth of endocrine tumours of the pancreas. Although information on somatostatin receptors has been provided recently, little is known on the receptor status of other gastrointestinal hormones in such tumours. AIMS: To analyse the spectrum of gut hormone receptors on endocrine tumours of pancreas. SUBJECTS: Four types of endocrine tumours from eight patientS. METHODS: The receptors for bombesin, secretin, vasoactive intestinal peptide, cholecystokinin, and somatostatin have been visualised and quantified with storage phosphor autoradiography. RESULTS: Bombesin receptors were present in all five gastrinomas and two primary VIPomas. Secretin receptors were expressed in four primary gastrinomas and one primary VIPoma from pancreas. Vasoactive intestinal peptide receptors were identified in four primary gastrinomas and all VIPomas. Furthermore, all VIPomas expressed cholecystokinin-B (gastrin) receptors, whereas, gastrinomas did not contain cholecystokinin-B receptors. The receptors for somatostatin were detected in all gastrinomas and VIPomas. Both somatostatinoma and glucagonoma were negative for all five types of peptide receptors studied. CONCLUSIONS: Besides somatostatin receptors, most of gastrinomas and VIPomas also express receptors for bombesin, secretin, and vasoactive intestinal peptide.